2014
DOI: 10.1590/s0102-86502014001900007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of sugammadex and neostigmine on QTc prolongation in rabbits under general anesthesia

Abstract: PURPOSE:To compare the effects of sugammadex and neostigmine, used to antagonize the effects of rocuronium, on the QT c interval. METHODS:This study used 10 adult New Zealand white rabbits of 2.5-3.5 kg randomly divided into two groups: sugammadex group (Group S, n:5) and neostigmine group (Group N, n:5). For general anesthesia administering 2 mg/kg iv propofol and 1 mcg/ kg iv fentanyl, 0.6 mg/kg iv rocuronium was given. Later to provide reliable airway for all experimental animals V-Gel Rabbit was inserted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Erbaş et al compared the eff ects of sugammadex and neostigmine for QT prolongation in rabbits under general anesthesia. Although sugammadex didn't have any infl uence, neostigmine increased the QT time 23 . Koyuncu et al reported that extubation, fi rst eye opening and head lift times were shorter in patients given sugammadex.…”
Section: Discussionmentioning
confidence: 91%
“…Erbaş et al compared the eff ects of sugammadex and neostigmine for QT prolongation in rabbits under general anesthesia. Although sugammadex didn't have any infl uence, neostigmine increased the QT time 23 . Koyuncu et al reported that extubation, fi rst eye opening and head lift times were shorter in patients given sugammadex.…”
Section: Discussionmentioning
confidence: 91%